Kepatuhan Minum Obat Antidiabetika Oral Pasien Ulkus Diabetikum Rawat Jalan di Klinik X Kota Pontianak Menggunakan Metode Kuantitatif - Prita Laoura; Nurmainah Nurmainah; Ressi Susanti (Indonesian Journal of Pharmaceutical Education, 2023)
Non-communicable diseases (PMT) have increased globally and nationally which have occupied the top ten causes of death with the most cases being diabetes mellitus. Diabetes Mellitus is a chronic disease that occurs due to impaired insulin action which causes blood sugar levels to increase. Uncontrolled sugar levels cause complications, one of which is diabetic ulcers. This study aims to analyze the level of adherence in taking medication in patients and the factors that influence adherence in taking medication in diabetic ulcer patients at Clinic Pontianak. The method used in this research is analytic observational method with the research design used is a cohort study. Compliance with drug use was measured using the Medication Possession Ratio (MPR) method. Data collection was carried out retrospectively based on manual and electronic data collection (medical records) and outpatient diabetic ulcer patient prescriptions at the Clinic Pontianak from January to December. Analysis of compliance relationship data using the chi square test. The results of this study showed that patients tended to be 45 years old (16.7%), female sex (87.5%), and monotherapy regimen (87.3%), this stated that there was no significant relationship between compliance with patient characteristics. Based on the results of the research, the percentage of compliance with the use of oral anti-diabetic drugs in outpatient diabetic ulcer patients at the Pontianak Clinic  in 2021 is 26.1%.